Program “JELAS” (Jajan Sehat dan Pilah Sampah): Meningkatkan Pengetahuan dan Perilaku Siswa - Ni Luh Putu Dian Yunita Sari; Prastikanala, I Kadek; Dharmawan, I Gd. Wahyu Dani (Synergy and Society Service, 2025)
School-age children are highly susceptible to infectious and non-communicable diseases. The causative factor of this disease risk is clean and healthy living behaviour, especially in food selection and waste management. The aim of this community service programme is to improve students' knowledge and behaviour in selecting healthy snacks and sorting waste. This programme offers education related to the selection of healthy snacks and waste sorting, storytelling the storybook “Ana and Adi”, and hands-on simulation. Evaluation of structure, process, and results was carried out in this community service. The structure evaluation was conducted to see the readiness of the team in implementing the programme. Process evaluation was conducted to see the number of partners present during the activities. In addition, an outcome evaluation was conducted to see changes in partners' knowledge and behaviour. The results obtained were an increase in the average knowledge and behaviour of students in choosing healthy snacks and sorting waste between before and after the program. This result is expected to be a guideline for schools and UKS programme holders to provide interventions to groups of primary school children in maintaining personal hygiene, the environment, and choosing healthy snacks. These results can also be used as a basis for disseminating health education media more widely in the community.